STRUCTURE OF SOME DEEP REGIONS OF THE HUMAN CEREBELLAR VERMIS WHITE-MATTER - Степаненко О. Ю. (World of Medicine and Biology, 2014)
Eight branches of the white matter form ten lobules of the cerebellar vermis. The first branch forms the first lobule, lingula. The second and third branches form the central lobule (lobule II and III). The fourth branch is the basis of the culmen, lobules IV-V. The fifth branch forms neocerebellar lobules - declive, lobule VI, folium vermis, lobule VIIa, and the tuber vermis, lobule VII B. The sixth branch forms a lobule VIII, pyramis. The seventh branch - uvula, lobule IX. Eighth branch forms nodulus, lobule X. Sometimes two or three branches begin with common portion of white matter. Purpose - to determine the structure of regions of white matter of the cerebellum that are common to several of its branches. 230 cerebella - the object of study, age 20-99 years. The cerebellum was dissected strictly on the central sagittal plane and photographed. Digitized images were analyzed. Results. The third branch in half of the cases starts with the fourth branch. Common origin of the two branches does not have own leaf of gray matter. Common trunk has one or two leaf of gray matter. One leaf is marked in 45%; in 25% it is located on the superior surface of 20% - at the inferior one. Two leaves meet in 35%, of which 30% are laid one on both sides, and 5% were both on the lower side. The fifth and sixth branches begin with common portion of white matter in 28% of cases. Common origin of the two branches does not own leaf of gray matter. Common trunk of the two branches having from one to three sheets. One sheet lies on the upper surface. Two pieces are typically located on one of the top and bottom surfaces. When the trunk has three leaves, always two lie on the upper surface and one - on the bottom. When four sheets, there is a symmetrical arrangement of the top and bottom sheets. In a few observations found five and seven sheets of gray matter. In 8% of cases there is a trunk that is common to the sixth and seventh branches. On its lower surface always lies own leaf of gray matter. Most long trunk has its three own leaf. In half of observations, the three branches, the fifth, sixth and seventh, begins with a common section of the white matter. In 84% of the objects have two of their own leaves of gray matter lying usually mirror - one on top, one - from the bottom. Trunk of white matter common to the fifth and sixth branches starting from the trunk common to the fifth, sixth, and seventh branches half the cases. It has from one to three layers. Only own a piece is always on the top surface. Two sheets of gray matter usually lie on the upper surface. When the sheets on the trunk of three, two always lie above and one below. Trunk, common for the sixth and seventh branches, in 37% starting from the trunk, common for the three branches. It has one or two own leaf.Discussion. The results show that the composition of the white matter cerebellum can distinguish portions that are common to two or three branches, which in the sagittal section can be described as trunks. Offered their names. Thus, the trunk, common for the third and fourth branches - truncus communis r. paleocerebellaris superioris III-IV, or truncus paleocerebellaris superior. Since rays of branches form lobules III and IV-V, it can be designated as a truncus communis ll. III-V. Trunk, from which begin with the fifth and sixth branches - truncus communis r. V-VI, or truncus communis ll.VI-VIII. The trunk common for the sixth and seventh branches - truncus communis paleocerebellaris inferior, or truncus communis r. VI-VII, or truncus communis lobules VIII-IX. Trunk, from which start with three branches, the fifth and sixth and seventh, - truncus communis r. V-VII, or truncus communis lobules VI-IX.
Keywords: cerebellum; wight substance; worms; cortex